The Influence of Conflict Management Style on the Satisfaction of Student Institution Management - Saleh, Sirajuddin; Karaeng, Juliani; Akib, Haedar (Asha Publishing, 2024)
The conflict management style in the organization is a management strategy in dealing with conflicts that occur. The use of an appropriate conflict management style will have a good impact on the organization. This study aims to find out the influence of conflict management style on the satisfaction of student institution administrators at the Faculty of Social Sciences and Law, Universitas Negeri Makassar. This study is a quantitative research that shows cause and effect. The sample in this study was 82 people with the Simple Random Sampling technique and 5 informants. The data collection techniques used are observation, questionnaires, interviews, and documentation. The data analysis techniques used are descriptive data analysis and inferential statistical analysis. The results of the study show that the conflict management style of student institutions at the Faculty of Social Sciences and Law, Universitas Negeri Makassar is in the